2023
DOI: 10.1242/dev.201705
|View full text |Cite
|
Sign up to set email alerts
|

The in vivo functional significance of PUF hub partnerships in C. elegans germline stem cells

Abstract: PUF RNA-binding proteins are conserved stem cell regulators. Four PUF proteins govern self-renewal of C. elegans germline stem cells together with two intrinsically disordered proteins, LST-1 and SYGL-1. Based on yeast two-hybrid results, we proposed a composite self-renewal hub in the stem cell regulatory network, with eight PUF partnerships and extensive redundancy. Here, we investigate LST-1–PUF and SYGL-1–PUF partnerships and their molecular activities in their natural context – nematode stem cells. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(23 citation statements)
references
References 72 publications
0
23
0
Order By: Relevance
“…All except lst-1(ø) harbor a C-terminal 3× V5 tag (inverted triangle). LST-1 (CΔ) deletes the C-terminal region ( amino acids 211 to 328); LST-1 (NΔ) carries a nonsense mutation early in LST-1L and makes only LST-1S, which lacks the N-terminal region unique to LST-1L (amino acids 1 to 94); LST-1 (ZnF) substitutes two key cysteines with serines (C260S and C263S, asterisks); LST-1(PIM), substitutes key amino acids for alanines in both PIM-A and PIM-B (L35A, K80A and L83A, asterisks) and abolishes LST-1 interactions with PUF proteins in both yeast and nematodes ( 15 , 16 ). ( B – I ) Boxplot and bar graph conventions as described in the Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All except lst-1(ø) harbor a C-terminal 3× V5 tag (inverted triangle). LST-1 (CΔ) deletes the C-terminal region ( amino acids 211 to 328); LST-1 (NΔ) carries a nonsense mutation early in LST-1L and makes only LST-1S, which lacks the N-terminal region unique to LST-1L (amino acids 1 to 94); LST-1 (ZnF) substitutes two key cysteines with serines (C260S and C263S, asterisks); LST-1(PIM), substitutes key amino acids for alanines in both PIM-A and PIM-B (L35A, K80A and L83A, asterisks) and abolishes LST-1 interactions with PUF proteins in both yeast and nematodes ( 15 , 16 ). ( B – I ) Boxplot and bar graph conventions as described in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We also asked whether the LST-1 PIMs affect either sygl-1 or lst-1 transcription. PIMs were already established as essential for posttranscriptional regulation ( 15 , 16 ), but a transcriptional role had not been tested. We found that both sygl-1 ATS and lst-1 ATS were comparable in lst-1(+) and lst-1(PIM) mutants ( SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations